What Determines the Interest in Investing to Gold Savings at Pegadaian Syariah? - Nur Masyithah; Ridwan Nurdin; Khairil Umuri; Hendra Halim (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2023)
Sharia pawnshops are a financial institution that plays an important role in society. One of the products offered is gold investment. This study examines the effect of knowledge and promotions mediated by motivation on interest in investing in gold in sharia pawnshops. The object of the study was carried out in Banda Aceh City with 100 respondents spread across 9 districts. Determination of respondents using purposive sampling technique and analyzed by path analysis model. The results found that there was a positive effect of knowledge and promotion on the motivation to invest in gold. Promotion and investment also have a positive effect on interest in investing in gold. Meanwhile, knowledge does not have a positive effect on interest in gold investment. Other results found that motivation is not able to mediate knowledge of interest in investing in gold. However, knowledge can be mediated by the motivation to invest gold in sharia pawnshops. So, sharia pawnshops must increase promotion and outreach to the community so that the gold investment products offered are increasingly in demand.